Spatiotemporal analysis of drought severity using SPI and SPEI: case study of semi-arid Borana area, southern Ethiopia - Worku, Mitiku Adisu (Frontiers in Environmental Science, 2024)
Drought is a complex natural hazard that can cause damage to socio-economic and biophysical systems in any climatic region. The main objective of this paper was to analyze the spatiotemporal drought in the semi-arid Borana area of southern Ethiopia from 1981 to 2018. The climate data was obtained from the Ethiopian Meteorological Institute. Standardized precipitation index (SPI) and Standardized Precipitation Evapotranspiration Index (SPEI) at 3- and 12-month timescales were adopted to characterize drought during these periods and wet seasons in time and space. The results revealed that moderate to extreme drought conditions at various stations frequently hit months stretching from March to June and September to November. The years 1984, 1985, 1992, 1999, 2000, 2001 and 2011 were known to be the driest years, among others. A total of 484, 563, 573 and 620 combined moderate, severe and extreme drought events were observed across all stations using SPI-3, SPEI-3, SPI-12 and SPEI-12, respectively. Internal variability among the stations was noticed regarding the frequency and magnitude of drought. Ganna (March to May), the season that was supposed to be the main rainy season in the region, was by far drier than Hagayya (September to November), the short rainy period. In general, this study found a high frequency and intense magnitude of drought that varies across the stations. Therefore, any localized adaptation and mitigation strategies intended to tackle or minimize drought-associated impacts should take into account this local variability.